Healthcare providers balancing norms and practice: challenges and opportunities in providing contraceptive counselling to young people in Uganda - a qualitative study - Mandira Paul; Sara B. Näsström; Marie Klingberg-Allvin; Charles Kiggundu; Elin C. Larsson (Taylor & Francis Group, 2016)
Background: Pregnancies among young women force girls to compromise education, resulting in low educational attainment with subsequent poverty and vulnerability. A pronounced focus is needed on contraceptive use, pregnancy, and unsafe abortion among young women. Objective: This study aims to explore healthcare providers' (HCPs) perceptions and practices regarding contraceptive counselling to young people. Design: We conducted 27 in-depth interviews with doctors and midwives working in seven health facilities in central Uganda. Interviews were open-ended and allowed the participant to speak freely on certain topics. We used a topic guide to cover areas topics of interest focusing on post-abortion care (PAC) but also covering contraceptive counselling. Transcripts were transcribed verbatim and data were analysed using thematic analysis. Results: The main theme, HCPs' ambivalence to providing contraceptive counselling to sexually active young people is based on two sub-themes describing the challenges of contraceptive counselling: A) HCPs echo the societal norms regarding sexual practice among young people, while at the same time our findings B) highlights the opportunities resulting from providers pragmatic approach to contraceptive counselling to young women. Providers expressed a self-identified lack of skill, limited resources, and inadequate support from the health system to successfully provide appropriate services to young people. They felt frustrated with the consultations, especially when meeting young women seeking PAC. Conclusions: Despite existing policies for young people's sexual and reproductive health in Uganda, HCPs are not sufficiently equipped to provide adequate contraceptive counselling to young people. Instead, HCPs are left in between the negative influence of social norms and their pragmatic approach to address the needs of young people, especially those seeking PAC. We argue that a clear policy supported by a clear strategy with practical guidelines should be implemented alongside in-service training including value clarification and attitude transformation to equip providers to be able to better cater to young people seeking sexual and reproductive health advice.